What Is Happening Where? An Evaluation of Social Science Research Trends in Nunavut (2004-2019) - Polidoro, Alexis (My University, 2022)
Many Inuit feel they are not benefitting from research activities that come from colonial research licensing practices and laws enabling state control over research. In Nunavut, research licensing also helped to increase community engagement in research. The Nunavut Research Institute (NRI), based in Iqaluit, Nunavut manages research and issues physical/natural, health, and social science research licenses in the Territory. In partnership with the NRI, we examined social science and Inuit knowledge research licensed between 2004-2019, to understand the scope of research trends in Nunavut. Using the 568 project summaries from social science research licenses, thematic content analysis was conducted to: i) identify research topics in social science and Inuit knowledge projects; ii) determine frequency and diversity of topics according to leadership, location, and timeframe; iii) develop new metrics to improve tracking of research topics; and, iv) contribute to the development of a Nunavut research portal making NRI research applications/reports public. Through this analysis we learned that social science research in Nunavut increased over time. Research projects are predominantly led by Canadian academics, with the highest concentration of research being in Iqaluit. Social science research is mainly focused on cultural topics, conducted using interviews, and shared in peer-reviewed journal articles. Community engagement has also increased over time in Nunavut, and research intensity appears to be connected to the availability of research-related capacity and infrastructure in a community. This research is an important starting point in making research trends more accessible to Nunavummiut (people of Nunavut), and more useable by decision-makers regarding research intensity and potential fatigue in some Nunavut communities. Long term, improving tracking of metrics such as funding sources and reporting mechanisms can contribute to policy reform and to advancing the NRI licensing database. This is an initial step contributing to Nunavut-specific approaches to Inuit self-determination in research.
Keywords: Inuit self-determination; trend analysis; northern studies; community engagement